The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1939-4551-7-19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and triggers of allergic rhinitis in the United Arab Emirates

Abstract: Background and objectivesAllergic rhinitis is a morbid condition that is frequently overlooked by patients and physicians. This type of atopy has not been adequately investigated in the United Arab Emirates.MethodsThis cross-sectional, population-based observational study was conducted in the seven Emirates (Abu Dhabi, Dubai, Sharjah, Ajman, Umm Al-Quwain, Ras Al-Khaimah, and Fujairah). It used the European Community Respiratory Health Survey (ECRHS II) to screen for allergic rhinitis in people living in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
2
19
1
Order By: Relevance
“…Similarly, based on the results of a study in the UAE, 71% of the patients with allergic rhinitis were sensitive to environmental allergens. Moreover, the findings demonstrated that 44% of the patients were sensitive to grass (20), which is consistent with the results of the current study. Bunnag et al showed that in the recent years, allergic rhinitis has increased by around three times in Thailand, and reported mites and grass as the most important agent of indoor and outdoor pollution, respectively (12).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, based on the results of a study in the UAE, 71% of the patients with allergic rhinitis were sensitive to environmental allergens. Moreover, the findings demonstrated that 44% of the patients were sensitive to grass (20), which is consistent with the results of the current study. Bunnag et al showed that in the recent years, allergic rhinitis has increased by around three times in Thailand, and reported mites and grass as the most important agent of indoor and outdoor pollution, respectively (12).…”
Section: Discussionsupporting
confidence: 92%
“…Most patients presented with sensitisation to weed pollen, followed by Dermatophagoides and Plumage, in our study. These data depend on the flora and climate of the region and environmental conditions (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Yet it was possible to reduce the margin of error by comparing the terminology of the study to other studies in the region. For example, the study that conducted in United Arab Emirates regarding allergic rhinitis and pollutants [4]. As both Kuwait and United Arab Emirates share same language, cultrate, demographical constitutes and geographically sharing similar features.…”
Section: -35yrs 36-50yrs > 50yrsmentioning
confidence: 99%
“…In the Middle East a study conducted in United Arab Emirates, (7%) of the studied population had an experience of allergic rhinitis [4].…”
Section: Introductionmentioning
confidence: 99%